Get them to Click it! Increasing Online Survey Response Rate - Ryan Chung (Academic Chairpersons Conference Proceedings, 2018)
In this interactive presentation, the presenter will be addressing challenges in administering online surveys and offering 20 strategies that may help attendees improve online survey response rates. At the end of this session, attendees should be able to identify several strategies to utilize in their own online survey data collection.
Keywords: Online survey; Higher Education; Data Collection; Administration; Survey Techniques